Protein Supplement Perceptions, Use, and Associated Performance in Young Lebanese Resistance-Training Athletes - Khadije K. Saleh; Sofi G. Julien (Journal of Nutrition and Metabolism)
The aims of this study were first to evaluate the nutritional knowledge, perception, and source of nutrition information among resistance-trained individuals consuming protein supplements (PS), to determine whether a correlation exists between nutrition-related knowledge and the use of PS, and finally to compare the impact of PS use among participants classified as nonprotein supplement users (NPSUs) and protein supplement users (PSUs). A cross-sectional study was conducted among a highly selected group of resistance-specialized trainees (RSTs). Among the 100 RST participants recruited, the Internet and coaches were the most common source of nutritional information. About one-third of participants believed that there were no health risks after consuming PS. Both NPSU and PSU exhibit performance improvement that was significantly lessened in PSU compared to NPSU. This study demonstrated that RST may have misconceptions regarding the benefits of PS usage to increase strength. Our data also suggest a shortage of knowledge about PS and confirm that PSUs lack proper professional guidance. These findings highlight the need for proper monitoring to ensure adequate perception, awareness, and safety in the Lebanese sports sector.